Mangifera indica L. extract tablets supplementation in patients with knee osteoarthritis pain. A controlled pilot study - Bárbara B. Garrido-Suárez; Gabino Garrido; Ana M. López-Mantecón; Octavio Piñeros; Jose M. Castro-Lopes; Rene Delgado-Hernández (GarVal Editorial Ltda., 2022)
Context: Several experimental results and clinical reports using Mangifera indica L extract (MSBE) suggest its potential utility in osteoarthritis (OA) mixed pain. Aims: To examine the possible therapeutic effects and safety of supplementation on osteoarthritis (OA) pain. Methods: Fifty patients with painful knee OA who had undergone a year of conventional treatment that included paracetamol and non-pharmacological therapies were randomly allocated to the experimental group (n = 21), which received a daily dose of 900 mg of extract supplementation or preceding usual treatment and placebo in the same form (n = 17) for a period of 120 days. The primary measure outcome was the change in the average daily pain diary score (ADPS) using the Likert scale. Also, a multidimensional measure of pain, stiffness and functional disability on The Western Ontario and Mc Master Universities (WOMAC) index for knee OA and ultrasonographic chronic signs of synovitis such as effusion and synovial thickness were evaluated. Results: Change from baseline in ADPS of the MSBE supplemented group showed a significant reduction after two weeks that lasted for 120 days with respect to the placebo group. Significant improvements in pain and functional disability WOMAC sub-scores, number of joints with synovial thickness and effusion after MSBE supplementation vs. placebo were observed. Non-adverse effects were reported in the experimental group. Conclusions: These results suggest that MSBE supplementation has a beneficial effect on OA pain and disability.